Tinjauan Hukum Islam Terhadap Praktek Gadai Kebun Cengkeh Di Desa Pegayaman, Kecamatan Sukasada, Kabupaten Buleleng, Bali - Rizal, Ketut Iqbal; , Dr. Muhammad Muhtarom, SH, MH (2016)
The minithesis writing is related to practice of clove plantation pawning occurred in Pegayaman village, Kecamatan Sukasada, Buleleng Regency, Bali province. The research is interesting because the use of security by pawnbroker (murtahin) and existence of requirements that are not conforming to Islamic law. Focus of the research is problem about what is the pawn practice? How does Islamic law review about the pawn practice? The research is field one conducted in Pegayaman village, Kecamatan Sukasada, Buleleng Regency, Bali province. The research is descriptive one, namely researcher explains data that is found in field and provides evaluation form sharia perspective. The research uses normative approach, researcher analyzes problem based on norms contained in Islamic law with Al-Qur'an and hadiths as sources, and also uses relevant principles of Islamic law. Data of the research was collected by performing interview with relevant parties. Based on research in the field, researcher concluded that practice of clove plantation pawning in Pegayaman village, Kecamatan Sukasada, Buleleng Regency, Bali province between pawner (rahin) and pawnbroker (murtahin) was in opposition to Islamic law because: first, there was a forcing element within the agreement, namely if rahin does not give his clove plantation harvest to murtahin, so murtahin will not lend money to him; second, there was riba element in the pawn practice, namely murtahin takes benefit exceeding limits from rahin.; third, the use of security goods (marhun) completely by murtahin, it should be that murtahin only takes benefit comparable to maintenance and operational costs if the clove plantation is indeed requiring the costs. Murtahin was also using marhun without profit-sharing with rahin. The complete use of security goods by pawnbroker is not approved by Islamic law because it means opportunistic principle. Also, the practice was no maintaining justice values and, in fact, the clove plantation was still owned by rahin.